Modifying the University Classroom to Increase Energy Expenditure in College Students - Peterson, Nolan; Thewis, Christopher; Charette, Jacob; Forsting, Shane; Grosskreutz, Luke (My University, 2011)
The purpose of this study was to determine whether energy expenditure can be increased by modifying a traditional-seated learning environment into a standing/activity permissive environment in college students.
Color poster with text, tables, graphs, and images.
Keywords: College students--Health and hygiene; Classroom environment--Health aspects; Obesity prevention; Posters